Eficiencia de bioabsorción de cáscara de coco (Cocos nucifera L.) para remoción de grasas y aceites en agua residual de lubricadora - Parrales Falcones, Anthony Leonardo (2024)
The objective of this research was to evaluate the efficiency of coconut shell (Cocos nucifera L.) for the removal of fats and oils in wastewater from the “La Sin Par” lubrication plant, through the application of experimental research. It was carried out in three phases: the first consisted of the characterization of the residual water in order to identify the contaminants in the lubricator. Subsequently, a filter was made with the shell of (Cocos nucifera L.) as a filter medium for the removal of fats and oils. The third phase focused on determining the biosorption efficiency of the filter medium. As a result, the average concentration of fats and oils before filtration was 77,17 mg/L, 386 mg/L Pt/Co color, pH 7,52 and 46,53 NTU in turbidity. The flow rate for treatment 1 was 0.48 L/h, with a hydraulic retention time of 4 hours and 0,35 L/h for treatment 2 with a hydraulic retention time of 5,48 hours. After filtering, the values of fats and oils dropped to 16 mg/L, having a removal efficiency of 78% for treatment 1 and 77% for treatment 2, accepting the hypothesis posed where the coconut shell-based filter removes more than 50% of fats and oils from the “La Sin Par” lubricator.